A method for eliminating the disturbance of pseudo-textural-direction in ultrasound image feature extraction. (January 2022) - Zhao, Yanan; Zhang, Dong; Lin, Liping; Yang, Yan
Highlights: A kind of short arc-like texture pattern brings disturbances to ultrasonic image processing was discovered. The formation of this disturbing directional texture pattern was investigated and illustrated. A novel feature extraction algorithm was developed to eliminate this disturbances. The algorithm was tested under effective features screening and tumor segmentation experiment. Improved efficiency was achieved without compromised image quality. Abstract: Ultrasound imaging is widely used in clinical diagnosis. However, due to the mechanism of B-mode sector scanning in ultrasound imaging, there exists pseudo-textural-direction (PTD) that is perpendicular to the ultrasonic beam and varies with the change of the beam scanning angle. The existence of PTD reduces the resolution of the image, and brings disturbances to subsequent tasks such as feature extraction, feature screening and segmentation. A method proposed to eliminate the disturbance of PTD consists of three stages. Firstly, a Fourier transform is performed on every superpixel that is a small homogeneous region generated by over-segmentation to obtain a spectrum of the superpixel. Then, ellipse fitting is conducted on the spectrum to detect the deflection angle of textural direction in the superpixel. Finally, the textural direction of the superpixel is corrected by the obtained deflection angle and the co-occurrence matrix texture features are extracted. The effectiveness of the proposed method was verified by segmentation experiments of ultrasound guided images of uterine fibroid acquired from high intensity focused ultrasound (HIFU) therapy based on a split and merge framework. The experimental results were evaluated by quantitative metrics that include true positive (TP), false positive (FP), similarity (SI), Hausdorff distance (HD) and mean absolute distance (MAD). All the metrics were improved in comparison with conventional algorithms when the features screening and segmentation algorithms worked with the proposed feature extraction algorithm. Therefore, the existence of PTD is demonstrated and the proposed method to eliminate its disturbance is feasible.